60 Multi organisational audit of the record and prompt for adult care in the last days of life in wirral. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Hayle, Catherine; Purewal, Gursaran; Longford, Emma; Ahmad, Fawad; Latten, Richard; Lunt, Carla-Jayne; Evans, Daniel; Brown, Clare; Shephard, Penny; Littlewood, Jill; D'Amelio, Nicola
Abstract : Background: The Wirral Multidisciplinary Record and Prompt for Adult Care in the Last Days of Life was developed in 2016 to support the delivery of excellent individualised care in last days of life in keeping with the Priorities for Care of the Dying Person and NICE guidance for Care of Dying Adults in the Last Days of Life. Following its introduction across Wirral University Teaching Hospitals NHS Foundation Trust and Wirral Hospice St John's, audits were undertaken across both settings assessing whether care in the last days of life was delivered and documented in line with national guidance. Method: A retrospective case note review was conducted using a standardised data collection tool. In the hospital setting, the audit sample from January-March 2017 included 30 cases where care was supported with the record of care, and 29 cases where it was not. In the hospice setting the audit sample from June-September 2016 included 34 patients whose care had been supported using this tool with comparison to a previous audit in 2015 assessing care in the last days of life. Results: The results across both organisations showed a considerable improvement in care delivered to patients in the last days of life, when the record of care was used, as evidenced by key findings in table 1 and 2. Conclusion: The use of the record of care has led to meaningful improvements in the care documented for dying patients and those close to them across all domains. The tool has been embedded across both organisations, with the focus now on ongoing education, awareness-raising of the improvement seen when the tool is used, and developments of electronic templates to support its use. Roll-out across the community setting is planned during 2018, with the aim of assuring the same high quality care in any setting.